Performance Of Financial Institutions In Five Sub-Saharan African Countries - Irbad, Husein Mohamed; Jayaprakash, M. G. (Archives of Business Research, 2020)
The purpose of this study is to investigate the performance of financial institutions in five Sub-Saharan African countries: Kenya, Nigeria, Namibia, Rwanda and Senegal. The investigation is based on four proxies towards performance namely: financial access, financial depth, financial efficiency and financial stability. The overall proxies are composed of thirty variables. There are four objectives in the study; the first objective has examined access and information of financial services in financial institutions of Sub-Saharan African countries. The second objective investigated and measured depth of financial institutions. The third objective evaluated efficiency of financial institutions in Sub-Sahara Africa. The last objective was intended to measure the stability of financial institutions in Africa. We created a development of financial performance model describing the proxies and variables in this study. The main analysis of the study is Mean calculation and regression analysis by using weighted Least Squares multiple regression analysis (WLS). This study investigated secondary data. The data was analyzed by using Excel software and Statistical Package for Social Sciences (SPSS) in descriptive statistics. The result of all target countries except Nigeria is significant in financial access. Result also showed significance in financial depth of all five target countries. The financial institutions of all five target countries are inefficient. Also the result of financial stability in financial institutions of target countries showed insignificance except Rwanda.